2014
DOI: 10.1007/s12011-014-0181-7
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Zinc Supplementation Beneficially Affects Seizure Development in Experimental Seizure Models in Rats

Abstract: The role of zinc in seizure models and with antiepileptic drugs sodium valproate (SV) and phenytoin (PHT) was studied using experimental models of seizures in rats. Male Wistar rats, 150-250 g were administered zinc 2, 20, and 200 mg/kg, orally for 14 days. Sixty minutes after the last dose of zinc, rats were challenged with pentylenetetrazole (PTZ, 60 mg/kg, ip) or maximal electroshock (MES, 70 mA, 0.2 s duration). In another group, SV (150/300 mg/kg, ip) or PHT (40 mg/kg, ip) was administered after 30 min of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Our work clearly shows that experimental Zn 2+ supplementation prolonged the seizure latency and elevated the seizure threshold. Although, there is not enough research to examine Zn 2+ supplementation in the seizures treatment, our findings are similar to the results of Kumar et al (11). However, it is unclear whether Zn 2+ supplementation modulates one or both of these parameters.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our work clearly shows that experimental Zn 2+ supplementation prolonged the seizure latency and elevated the seizure threshold. Although, there is not enough research to examine Zn 2+ supplementation in the seizures treatment, our findings are similar to the results of Kumar et al (11). However, it is unclear whether Zn 2+ supplementation modulates one or both of these parameters.…”
Section: Discussionsupporting
confidence: 87%
“…Studies of the pathogenesis of febrile seizures (FSs), the most common type of seizure in children, found that Zn 2+ levels were low in both the serum and the CSF (16). The effect of Zn 2+ treatment in different experimental seizure models have been evaluated by Kumar H. et al (11). This study has shown that the lowest dose Zn 2+ supplementation in pentylenetetrazole (PTZ) seizure model has a protective effect and the Zn 2+ pretreatment in maximal electroshock (MES) model has no effect.…”
Section: +mentioning
confidence: 99%
“…In those patients, zinc supplementation significantly reduced seizure frequency and when the zinc supplement was discontinued, the seizure activity recurred (24). There is also some evidence that zinc supplementation decreases seizure activity in experimental seizure models in rats (25). Additionally, there are a few case reports in human epileptics documenting a selenium deficiency that improved with selenium supplementation (12,21,26).…”
Section: Discussionmentioning
confidence: 99%
“…Low zinc levels are associated with decreased cell survival, altered neuronal differentiation, and, in particular, synaptic function. 16 The lower zinc concentration is related to aging and to some pathological events like amyotrophic lateral sclerosis, 17 aluminium-induced neurodegeneration, 18 epilepsy, 19 and the beneficial effects of zinc supplementation is documented in these cases. A low zinc bioavailability during aging has been linked to abnormal increments of zinc-bound MTs in hippocampus of old rats.…”
Section: Introductionmentioning
confidence: 99%